Relationships of self-perceived age with geriatric assessment domains in older adults with cancer. Issue 6 (July 2020) - Loh, Kah Poh; Duberstein, Paul; Zittel, Jason; Lei, Lianlian; Culakova, Eva; Xu, Huiwen; Plumb, Sandy; Flannery, Marie A.; Magnuson, Allison; Bautista, Javier; Wittink, Marsha; Gilmore, Nikesha; et al.
Abstract: Objectives: Older self-perceived age is associated with poor health and higher healthcare utilization in the geriatric population. We evaluated the associations of self-perceived age with geriatric assessment (GA) domain impairments in older adults with cancer. Methods: This was a secondary analysis of baseline data from a GA cluster-randomized trial (URCC 13070; PI: Mohile). We included patients aged ≥70 with incurable stage III/IV solid tumor or lymphoma considering or receiving treatment and had ≥1 GA domain impairment other than polypharmacy. Multivariate analyses were used to evaluate the associations of age difference between chronological and self-perceived age (categorized into "feeling younger than chronological age" vs. "feeling the same or older than their chronological age") with GA domain impairments. Results: We included 533 patients; mean age was 76.6 (SD 5.2). On multivariate analyses, compared to those who felt younger than their chronological age, those who felt the same or older were more likely to have impairments in physical performance [Adjusted Odds Ratio (AOR) 5.42, 95% Confidence Interval (CI) 1.69–17.40)], functional status (AOR 2.31, 95% CI 1.73–3.07), comorbidity (AOR 1.62, 95% CI 1.20–2.19), psychological health (AOR 2.62, 95% CI 1.85–3.73), and nutrition (AOR 1.65, 95% CI 1.20–2.28). They were also more likely to screen positively for polypharmacy (AOR 1.86, 95% CI 1.30–2.65). Conclusions: Older adults with cancer who felt the same or older than their chronological age were more likely to have GA domain impairments. Further studies are needed to better understand the relationships between self-perceived age, aging-related conditions, and outcomes in this population.